Suomen suurimmat tilat talousvertailussa - Puurunen, Maija; Remes, Katariina (MTT, 2002)
Suuren tilan määritelmä ei ole yksiselitteinen. Tässä tutkimuksessa suuriksi tiloiksi on rajattu tuotantosuunnittain kustakin maasta 10 % suurimmista maito- ja viljatiloista sekä 20 % suurimmista sikatiloista. Nämä rajaukset huomioon ottaen vuoden 1999 tietojen mukaan Suomen mittakaavassa suureksi maitotilaksi voidaan luokitella tila, jolla on peltoa viljelyksessä yli 65 ha ja lehmiä yli 34 kpl. Vastaavasti sikatila on suuri, jos peltoa on viljelyksessä yli 70 ha ja eläinyksiköitä yli 170. Suurella viljatilalla peltoa on oltava viljelyksessä vähintään 120 ha. Tilakoko Suomessa on kasvanut kovaa vauhtia, kuitenkin Suomen suuret tilat ovat vähintäänkin puolta pienempiä kuin Saksan, Tanskan ja Ruotsin suuret tilat. Tutkimuksessa tarkasteltiin keskeisenä tuloskäsitteenä nettoarvonlisäystä, joka on korvaus tehdylle vieraalle ja omalle työlle sekä vieraalle ja omalle pääomalle. Nettoarvonlisäys-käsitteen avulla voidaan verrata eri maiden samaa tuotantosuuntaa olevia tiloja. Tarkasteltavista kotieläintiloista nettoarvonlisäys oli suurin Tanskassa, 183 000 e/maitotila ja 250 000 e/sikatila, tuen osuus nettoarvonlisäyksestä oli neljännes. Viljatiloista nettoarvonlisäys oli suurin Saksassa, 310 000 euroa/tila, nettoarvonlisäyksestä 60 % oli tuotantotukia. Saksalaiset viljatilat olivat huomattavasti muita vertailuryhmiä suurempia. Suomen suurilla tiloilla nettoarvonlisäykset olivat 26 000-58 000 e/tila, joka oli kokonaan tukea

Farm size has increased rapidly in Finland. This study examines concepts and economic results of large farms in Finland, Sweden, Denmark and Germany. In this study a 'large farm' is defined as among the top 10 % by size for dairy or cereal farms or top 20 % by size for pig farms. According to this definition, a large Finnish dairy has over 65 hectares of fields and more than 34 cows. Correspondingly, a large pig farm would have a utilized agricultural area greater than 70 hectares and livestock units of more than 170. Farms specializing in cereal production are large if they have a utilized agricultural area greater than 120 hectares. Although farm size has increased in recent years, Finnish large farms are still less than half the size of large farms in Germany, Sweden or Denmark. In this study the most important standard result is net value added: that part of the total revenue that remains as salary for the farm family, for foreign labour, and for interest on total capital committed to production operations. The concept of net value added can be compared between farms in different countries that specialize in the same production line. The total output of large Finnish dairy farms increased 15 % 1997-1999. In spite of this, net value added remained at 53 000 ECU/farm and did not increase. Net value added was about the same size as subsidies. On the Danish milk farms net value added was 183 000 ECU/farm and 20 % of it consisted of subsidies. Net value added for large Finnish cereal farms was 26 000 ECU/farm. Subsidies for large cereal farms exceeded 57 000 ECU/farm, so more than half of subsidies went to cover costs. Net value added was highest on cereal farms in Germany. In Germany net value added was on cereal farms 310 000 ECU/farm and 60 % of it consisted of subsidies. Net value added for large Finnish pig farms was 58 000 ECU/farm. Subsidies paid to pig farms exceeded 76 000 ECU/farm, therefore a part of the support was needed to cover costs. Net value added was highest on pig farms in Denmark. On the Danish pig farms net value added was 250 000 ECU/farm and 20 % of it consisted of subsidies.
Keywords: Ma; tilakoko; maatalouden arvonlisäys; maidontuotanto; viljantuotanto; sianlihantuotanto; tuotantotuki; kansainvälinen vertailu; large farms; net value added; subsidies; dairy farm; pig farm; cereal farm; Finland; Sweden; Denmark; Germany